The need for the digitization of special library materials in Nigerian university libraries (2010)
Digitization as a method of preservation is now a global phenomenon and the new trend in managing library information materials and content, especially precious ones. This paper positions Nigerian university libraries within this global context; identifies the benefits and parameters for digitizing special library materials; and investigates the pattern of usage of the special collections in Kenneth Dike Library (KDL), University of Ibadan, with the aim of establishing their suitability for digitization. The records of consultation of Africana, Publications Ordinance and Theses collections from 2004 to 2008 were surveyed. The record of foreign requests of Africana materials was also studied. A qualitative analysis of data using frequencies and percentages shows that, in spite of the general challenges of digitization, it is desirable to digitize the special collections in KDL. However, it is recommended that before embarking on digitization, a digitization programme should be drawn up with detailed prioritization mapped out. The KDL digitization project should start with digitizing the abstracts of the Theses collection